Tocilizumab-resistant TAFRO Syndrome Complicated by Type II Respiratory Failure - Aoki, Tatsuya (Intern Med, 2017)
A 66-year-old man with a several year history of thrombocytopenia, pleural effusion and ascites, anasarca, and organomegaly presented with general fatigue, appetite loss, dyspnea with type II respiratory failure. The precise history of the patient and the re-evaluation of lymph node and bone marrow biopsies conducted by the previous physician indicated TAFRO syndrome. The patient's laboratory data improved for a year with tocilizumab, but then worsened to the point that the patient required artificial ventilation due to the deterioration of type II respiratory failure. The replacement of tocilizumab with rituximab yielded a steady improvement, but it was necessary to address the patient's persistent respiratory failure. Peripheral nerve disorder might have been involved with the patient's respiratory failure.